Types of Steering and Their Design Aspects: Jenis Kemudi dan Aspek Desainnya - Rustamov, Kamoliddin Juraboevich; Tojiev, Lazizbek Orifjonovich (Universitas Muhammadiyah Sidoarjo, 2022)
This article provides information about steering mechanisms, their types and designs. It was also discussed in which vehicles these steering gear designs could be used.